The Quality of Education Personnel Services as a Supporting Indicator for the Successful Implementation of Merdeka Belajar-Kampus Merdeka - Sri Rahayu; Ayu Asmah; Denna Delawati Chrisyarani; Ika Meviana; Yulianti; Iskandar Ladamay (Universitas Kanjuruhan Malang, 2022)
MBKM has the aim of encouraging students to improve 21st century competencies and master various sciences, both hard skills and soft skills as a provision to enter the world of work. The Faculty of Education (FIP) has an active role in preparing graduates who are superior, creative, independent, tolerant, democratic and religious based on science and technology. This study aims to determine the role of tendik in the implementation of MBKM based on the dimensions of service quality. The research method used is an explanatory design with a survey method using a questionnaire as a data collection tool. Service quality coverage on five dimensions: Tangibles; Reliable; Responsiveness; Assurance/Guarantee; and Empathy. This research was conducted at FIP ​​Universitas PGRI Kanjuruhan Malang with a population of 34 lecturers. The results of the questionnaire survey on Tendik's satisfaction with the role of Tendik in the implementation of MBKM showed varied categories. The highest average percentage of each element, namely the responsiveness element in the very good category, is 88%.